Endothelial Dysfunction and Impaired Neurovascular Coupling Responses Precede Cognitive Impairment in a Mouse Model of Geriatric Sepsis - Csipo, Tamas; Cassidy, Benjamin R.; Balasubramanian, Priya; Drevets, Douglas A.; Ungvari, Zoltan I.; Yabluchanskiy, Andriy (Frontiers in Aging Neuroscience, 2021)
Sepsis is a life-threatening condition, the incidence of which is significantly increased in elderly patients. One of the long-lasting effects of sepsis is cognitive impairment defined as a new deficit or exacerbation of preexisting deficits in global cognition or executive function. Normal brain function is dependent on moment-to-moment adjustment of cerebral blood flow to match the increased demands of active brain regions. This homeostatic mechanism, termed neurovascular coupling (NVC, also known as functional hyperemia), is critically dependent on the production of vasodilator NO by microvascular endothelial cells in response to mediators released from activated astrocytes. The goal of this study was to test the hypothesis that sepsis in aging leads to impairment of NVC responses early after treatment and that this neurovascular dysfunction associates with impairments in cognitive performance and vascular endothelial dysfunction. To test this hypothesis, we used a commonly studied bacterial pathogen, Listeria monocytogenes, to induce sepsis in experimental animals (males, 24 months of age) and subjected experimental animals to a standard clinical protocol of 3 doses of ampicillin i.p. and 14 days of amoxicillin added to the drinking water. NVC responses, endothelial function and cognitive performance were measured in septic and age-matched control groups within 14 days after the final antibiotic treatment. Our data demonstrate that sepsis in aging significantly impairs NVC responses measured in somatosensory cortex during whisker stimulation, significantly impairs endothelial function in isolated and pressure cannulated aorta rings in response to acetylcholine stimulation. No significant impairment of cognitive function in post-sepsis aged animals has been observed when measured using the PhenoTyper homecage based system. Our findings suggest that sepsis-associated endothelial dysfunction and impairment of NVC responses may contribute to long-term cognitive deficits in older sepsis survivors.